Students’ Mathematical Critical Thinking Processes in Solving Algebraic Problems: A Qualitative Analysis Based on Watson–Glaser Indicators - Astuti, Merlina Dwi; Attin Warmi; Kiki Nia Sania Effendi (Jurnal Didactical Mathematics, 2026)
Mathematical critical thinking is a fundamental competence required for effective algebraic problem solving; however, many students experience difficulties that extend beyond procedural errors. This study aims to analyze junior secondary students’ mathematical critical thinking processes in solving algebraic problems based on the Watson–Glaser critical thinking indicators. Employing a qualitative descriptive design, the study involved 40 seventh-grade students from a public junior high school in Indonesia. Written test data were used to describe the overall distribution of students’ critical thinking levels, while in-depth qualitative analysis was conducted on three purposively selected students representing high, moderate, and low ability levels. Data were analyzed through indicator-based scoring and qualitative content analysis supported by interview data. The findings reveal that students’ mathematical critical thinking ability was predominantly low, with major difficulties in deductive reasoning and the evaluation of arguments. Qualitative results indicate distinct reasoning patterns across ability levels: high-ability students demonstrated coherent reasoning but weak communication of conclusions, moderate-ability students showed fragmented and inconsistent reasoning, and low-ability students relied heavily on intuitive guessing with limited conceptual understanding. These findings highlight the need for process-oriented, differentiated instructional strategies that explicitly foster critical thinking in algebraic learning.